2022
DOI: 10.34172/jlms.2022.48
|View full text |Cite
|
Sign up to set email alerts
|

Bone Neoformation Induced by Low-Level Laser and Methylene Blue Suggests Early Ossification in Rats

Abstract: Introduction: Bone healing depends on inflammation control and tissue repair time. Low-level laser therapy (LLLT) has been investigated to accelerate this process. Methylene blue (MB), together with LLLT, has been investigated for its antioxidant and anti-inflammatory potential; however, the effects of photosensitizers (photodynamic therapy, PDT) are controversial. This study aimed to verify whether the combination of MB and LLLT changes the course of the consolidation of experimental bone defects. Methods: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The combined therapy also enhanced radiopacity, suggesting improved bone healing. The study suggests that MB with LLLT may stimulate bone repair and could be beneficial for bone healing [ 23 ]. Using a rat model of osteoarthritis (OA), intra-articular MB injections significantly inhibited synovitis (inflammation), relieved pain, and prevented cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The combined therapy also enhanced radiopacity, suggesting improved bone healing. The study suggests that MB with LLLT may stimulate bone repair and could be beneficial for bone healing [ 23 ]. Using a rat model of osteoarthritis (OA), intra-articular MB injections significantly inhibited synovitis (inflammation), relieved pain, and prevented cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, attempts are being made to optimize bone regeneration through physical methods, promoting more effective morphophysiological rehabilitation in a shorter period. One of the recent techniques with reports of success in this area is low-level laser therapy-LLLT [49][50][51]. LLLT in bone tissue has been shown to be effective mainly in modulating the inflammatory response and accelerating the tissue repair process [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Research results showed that particular laser irradiation stimulated fibroblast proliferation without impairing procollagen synthesis. Also, since LLLT can modulate inflammatory processes in a dose-dependent manner, it can significantly reduce acute inflammatory pain (9,10). However, according to some studies, LLLT can reduce pain but does not affect accelerating wound healing.…”
mentioning
confidence: 99%